EFEKTIFITAS PENERAPAN COOPERATIVE LEARNING TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH MANAJEMEN KEPERAWATAN - Rauf, Syamsiah (Universitas Islam Negeri Alauddin Makassar, 2017)
Cooperative learning is one of learning method that can improve the quality of learning.This research aimed to evaluate the effects of the Cooperative Learning method on the students learning achievement.The research type was descriptive analytical with the cross-sectional approach. The samples were chosen from all the nursing students, who took the nursing management cource, using the total sampling technique. The data analysis used Pearson correlation test and One Way ANNOVA.The research results revealed that there was a correlation between the students perception towards the Cooperative Learning method and their learning achievement (p=0.001). pearson correlation value of 0.563 indicated a positive correlation with a strong effect. The result of the One Way Annova revealed the result that the learning interest towards the cooperative learning method was STAD, TGT and Jigsaw were significantly different from the value of 0.000 < 0.05. this indicated that the learning interest had a strong and significant correlation with the learning achievement. The higher the learning interest increased, the higher the learning achivement would be; and so would be the opposite. Then, in order to see the differences of the learning achievements of the different learning methods of cooperative learning, i.e. STAD, TGT, and Jigsaw, the further test, i.e. the post-hoc tukey test, it was found that the result of the Post-Hoc Tukey showed that the highest learning achievement was by using TGT learning method (the mean value was 91.42), followed by the jigsaw method (the mean value was 89.27), and by the STAD method (the mean value was 83,92). Thus, in order to increase the students learning achievements, the cooperative learning method, particularly the TGT method, could be used.